Radioaktivität in Fischen und anderen Meerestieren aus der Nordsee. Auswirkung der 1994 geänderten Genehmigung für Sellafield auf die Strahlenexposition der Bevölkerung - Kanisch, Günter; Nagel, Gunther; Krüger, Alois; Kellermann, Hans-Jürgen (2000)
A subject of a change of authorised limits in 1994 forthe discharge of liquid radioactive waste by the reprocessing plant Sellafield (UK) was an increase of theselimits for certain radionuclides (3H, 14C, 60Co, 99Tc and129I). It is investigated now how the radioactivity in marine biota from the North Sea and subsequently the publicradiation exposure by ingestion has developed in theyears since 1994. This is based on a compartment modelfor the Northeast Atlantic. Discharges of the reprocessingplants Dounreay (UK) and La Hague (F) are included in the assessment. It is deduced that about 60 % of 137Cs in the North Sea originate presently in the remobilisation of old Sellafield discharges from the Irish Sea sediment. A comparison with measured biota data shows that the model is conservative in the most cases. The public radiation exposure from ingestion of fish, crustaceans and molluscs from the central North Sea as the sum over 12 considered radionuclides has decreased from 1992 to 1998 from 0,13 to 0,08 μSv·y–1. For the southward and northward joined regions it was a little bit smaller with a similar decreasing trend. Johann Heinrich von Thünen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung = Information on Fishery research in 2010.